THE The Implementation of Audio Storytelling Activities in Teaching Speaking for Visual Impaired Students: A Narrative Inquiry Study in SLBN Handayani Sukabumi - Allifna Nur'Izzati Fajriah; Erni Haryanti; Predari Siswayani (ELITE JOURNAL, 2021)
Children start to learn about many things with something that they see and hear, visually impaired children need to adapt to their visual impairment and struggle to learn about such things. Thus, this research attempts to explore the implementation of audio storytelling activities in teaching English speaking for visual impaired students. The importance of this research is to analyse the teacher’s experience and the problems in implementing audio storytelling activities for visual impaired students speaking ability. This study uses qualitative method, especially using narrative inquiry design that involves a participant who was experienced in teaching to visual impaired students. The findings showed that in speaking aspects, there was a slight improvement after being treated by audio storytelling, students tend to be more exited in learning especially when they heard a story that they are interested in. they like to explore the story and discussed it in post-listening activities. Second, there are some important points that should be concerned by the policy makers, and the teacher of special need toward the teaching English for visual impaired students. In the term of audio storytelling the teacher needs to enhance and explore the English teaching materials and strategies that will be delivered to the students. Keywords: audio storytelling, speaking skills, visual impaired students